Early Results of a Novel Gutter-Free Chimney Stent-Graft System to Treat Aortic Arch Dissection: Single-Center Data from a Prospective Clinical Trial. (April 2022) - Shu, Chang; Li, Xin; Dardik, Alan; Li, Quanming; He, Hao; Li, Ming; Fang, Kun; Luo, Mingyao; Wang, Tun; Yang, Chenzi; Wang, Mo
Aims: Discuss the clinical value, technique characteristics, and early follow-up results of a newly designed gutter-free chimney stent-graft system for aortic arch pathology. Methods and Results: About 13 patients with aortic arch dissection were enrolled in a clinical trial testing a novel gutter-free stent-graft between February 2019 and December 2020. All 13 patients were male, age 52.6±10.4 years. The implantation time was 14.0±6.9 minutes; total procedure time was 89.5±19.8 minutes. The volume of contrast was 79.6±7.2 ml. And 15 aortic stent-grafts were implanted, and all 13 patients had chimney branch stent-grafts implanted into the left subclavian artery (LSA). There were 3 (23.1%) cases of immediate type Ιa endoleak after thoracic endovascular aortic repair (TEVAR), and 7.7% type Ιa endoleaks occurred in delayed fashion. Survival at 2 years was 100%, and the 2-year patency of chimney stent-grafts was 100%. Conclusions: This study reports early success with good freedom from endoleak using a novel stent-graft designed for chimney TEVAR to treat aortic arch dissection. Postoperative survival and patency of the branch stent-grafts were excellent. Additional data from this multicenter clinical trial will be forthcoming.